Elimination disorders in a group of South African children - Patel, Firuzan Harishkumar (My University, 2010)
Background: Elimination disorders are childhood behavioural disorders. In South Africa these disorders fall within a neglected field of study when compared to physical illnesses. This report serves as formative research in order to address this neglect. Aims: To identify and summarise the clinical presentations, age and gender distribution, associated comorbid disorders and psychosocial factors in our mainly black patients from Soweto, Johannesburg, South Africa. Methodology: One hundred and sixteen children aged 4 – 14 years with these conditions were enrolled into a descriptive prevalence or survey study over a period of three years. An interview questionnaire was explained and responses recorded, from the caregivers and subjects. Result: There were 72 males and 44 females and their mean age at presentation was 9 years. More males suffered from encopresis only and both elimination disorders than females. There was only one female with encopresis alone. More females had enuresis than males. A greater percentage of subjects had primary enuresis as compared to encopresis, which was predominantly secondary in nature. Mental retardation, learning disability and ADHD were common comorbid conditions. Conclusion: The prevalence of elimination disorders in children attending an outpatient paediatric facility does justify the need for a specialised elimination disorder clinic. This clinic needs to be accommodated within an ambulatory paediatric unit such as the paediatric outpatients department of the Chris Hani Baragwanath Hospital.
MSc (Med) Neurodevelopmental Paediatrics, Faculty of Health Sciences, University of the Witwatersrand
Keywords: enuresis; encopresis; elimination disorders; children